Surhetstillståndet i bäckar uppströms kalkdoserare i Dalarnas län - Khoussainova, Goulnara (SLU/Dept. of Aquatic Sciences and Assessment, 2010)
The acid deposition of sulphur- and nitrogenoxides from combustion of coal and oil cause acidification that lowers pH and gives increased contents of metals and altered aquatic biodiversity in the stream. The liming of lakes and streams, which was introduced to resist the acidification, demand large economic resourses despite of the decreased deposition of the acidifyng substances. Some of the streams are influenced by the acid deposition, while others are naturally acidic. It is therefore importaint to separate the anthropogenically acidified waters from the naturally acidic, in order to optimize the use of governmental fundings for liming. This thesis aims to estimate the acidity status and impact of acidification on 24 catchments upstream liming dispensers, which is part of the liming activities at the County of Dalarna.